2006
DOI: 10.1128/jcm.44.3.819-826.2006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MIC with Outcome for Candida Species Tested against Voriconazole: Analysis and Proposal for Interpretive Breakpoints

Abstract: Developing interpretive breakpoints for any given organism-drug combination requires integration of the MIC distribution, pharmacokinetic and pharmacodynamic parameters, and the relationship between the in vitro activity and outcome from both in vivo and clinical studies. Using data generated by standardized broth microdilution and disk diffusion test methods, the Antifungal Susceptibility Subcommittee of the Clinical and Laboratory Standards Institute has now proposed interpretive breakpoints for voriconazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
191
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 34 publications
7
191
2
2
Order By: Relevance
“…Furthermore, we have shown that the availability of posaconazole susceptibility testing results for Candida spp., in any medical center currently performing antifungal susceptibility testing of either fluconazole or voriconazole, can be accomplished by using the fluconazole or voriconazole result as a surrogate marker for posaconazole susceptibility and resistance. Arguably, the most important role of in vitro susceptibility testing is to predict the resistance of the infecting organism to the agent under consideration for use in the patient (32,33,37). The occurrence of false-resistance errors with this application of the "class representative" concept to the available triazoles was very low and was acceptable for surrogate marker testing.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, we have shown that the availability of posaconazole susceptibility testing results for Candida spp., in any medical center currently performing antifungal susceptibility testing of either fluconazole or voriconazole, can be accomplished by using the fluconazole or voriconazole result as a surrogate marker for posaconazole susceptibility and resistance. Arguably, the most important role of in vitro susceptibility testing is to predict the resistance of the infecting organism to the agent under consideration for use in the patient (32,33,37). The occurrence of false-resistance errors with this application of the "class representative" concept to the available triazoles was very low and was acceptable for surrogate marker testing.…”
Section: Resultsmentioning
confidence: 94%
“…The facts that both fluconazole and voriconazole are in the same triazole class as posaconazole, have Clinical and Laboratory Standards Institute (CLSI)-approved MIC interpretive breakpoints (32,33), and are available on some commercially available MIC panels (10,19,29,34,38) suggest that one or both of these agents may be useful as a surrogate marker for posaconazole susceptibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Using MIC data for voriconazole in over 8000 clinical isolates, the Antifungal Susceptibility Subcommittee of the Clinical and Laboratory Standards Institute has now proposed interpretive breakpoints for voriconazole and Candida species. 22 These are as follows: o1 mg/ml susceptible, 2 mg/ml susceptible dose dependent, and 44 mg/ml resistant. Although the majority of C glabrata isolates were susceptible to voriconazole, among the fluconazole-resistant isolates, 44% were susceptible to voriconazole in a dose-dependent manner (MIC 2 mg/ml).…”
Section: 04mentioning
confidence: 99%
“…However, reports of FL failure in similar groups of patients have also been documented (Marr et al, 2002;Saiman et al, 2000). Additionally, on exposure to FL, the levels of resistance can increase dramatically, which selects for drug-resistant subpopulations, leading to clinically significant FL resistance (Pfaller et al, 2006). C. glabrata is thought to acquire drug resistance as a result of its haploid nature and its ability to mutate rapidly following exposure to triazole-derived agents (Safdar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%